Early modern cultural transfers and cultural translations in the south Slavic contact zone: the example of Pavao Ritter Vitezović (1652-1713) - Blažević, Zrinka (Array, 2010)
Transcultural activity of Pavao Ritter Vitezović that was in the focus of this text apparently shows that cultural boundaries represent the interstitial zones of interaction, spaces of permeation and overlapping where cultural identities have been constantly (re)created in the contingent game of attraction and rejection. Contaminated with the otherness and difference, they always oscillate in paradoxical but insolvable double dichotomy between the "othered" self and the appropriated other. Consisting of relational cultural identities built upon the principle of reciprocal inclusiveness, South Slavic or wider Balkan contact zone might with good reason be conceptualized as the space of the (im)possible coexistence of displaced, translated and hybrid, but unique and extraordinary cultural forms.